The Impact of Educational Philosophy on The Development of Islamic Education Curriculum - Falaqi Muhamad Rizal; Nurkholisoh, Siti; Ansharah, Indana Ilma; Alfiyah, Nur; Tricahyo, Agus; Bahruddin, Uril (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: This research aims to rectify perspectives that overlook the significant contributions made by three important figures in educational philosophy to the advancement of the Islamic education curriculum. The objective of this research was to explain the implications of the ideas put out by three educational philosophy figures, namely John Locke, Henry Giroux, and John Dewey, in the development of the Islamic education curriculum. Each paradigm represents a distinct philosophical viewpoint: Humanism, Reconstructionism, and Progressivism. Methodology: The research methodology employed is qualitative content analysis approach, specifically based on a systematic literature review. The research model is to explain the perspectives of three major thinkers of educational philosophy. Findings: The findings of this study indicate that the three educational philosophy figures play distinct roles in the development of the Islamic education curriculum. John Locke advocated for the promotion of reason and ethical principles in the context of Islamic education. Henry Giroux enhances students’ capacity to critically examine material, comprehend social reality through an Islamic lens, and actively participate in meaningful discussions on significant matters. John Dewey enhanced the curriculum by prioritizing the cultivation of moral qualities and the practical utilization of knowledge in real-life situations. This philosopher introduced educational principles that became influential in the advancement of Islamic education, namely focusing on fostering reasoning and moral development, promoting critical thinking, and advocating for participatory learning. Implications/Novel Contribution: The implications of this study highlight the need for an Islamic education curriculum that integrates reasoning and ethical reflection, as advocated by John Locke. Henry Giroux’s ideas emphasize the importance of critical thinking and social awareness through an Islamic lens. John Dewey’s philosophy supports participatory and experiential learning to apply knowledge in real-life contexts. Together, these perspectives encourage a holistic, dynamic, and socially responsive Islamic education.